Imobilisasi Limbah Radioaktif dari Produksi Radioisotop Molibdenum-99 (99Mo) Menggunakan Bahan Matriks Synroc Titanat - Gunandjar Gunandjar; Titik Sundari; Yuli Purwanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
The Immobilization Of Radioactive Wastes Generated From Molybdenum-99 (Mo-99) Radioisotope Production Using Titanate Synroc Matrix Materials. The assessment of immobilization technology using synroc matrix material for the long life radioactive liquid wastes generated from Mo-99 radioisotope production containing of uranium, transuranic and fission product elementswas carried out. For that purpose have been developed the titanate synroc matrix material by hot isostatic pressing process. All basic science studies confirm that the leach-rates and a-decay damage in synroc relatively very low and acceptable.  In Indonesia, adaptation of immobilization technology using titanateof synroc matrix materials was carried-out for immobilization of the long life radioactive liquid wastes generated from 99Mo radioisotope production by sintering process at high temperature. Immobilization process was carried-out by mix the radioactive waste with  precursor oxides, then drying the mixture at 100 oC, calsination at 750 oC, then it was preesed in the moulder. Further process are  sintering at the temperature of 1000-1300 oC with the time 1-4 hours to form the solid multiphase ceramic. The composition of  precursor oxides for titanate synroc (in % weight) i.e :  Al2O3  (5.4);  BaO (5.6);  CaO (11.0); TiO2 (71.4) and ZrO2 (6.6). Waste loading in the waste synroc block are 10 – 60 % weight. The quality of the synroc block was determinated by testing of density, pressing strength, and leaching-rate. The testing results showed that the best quality of waste synroc block was obtained at the waste loading 20% weight, sintering process at 1200 oC for 3 hours with values of density 3.35 g/cm3, pressing strength 14.18 kN/cm2, total leaching-rate 2.5.10-3 g.cm-2.day-1 , and leaching-rate of Cs, Sr, and U are  4.1x.10-4 g.cm-2.day-1, 2.3x10-6 g.cm-2.day-1 and 6.3x10-7 g.cm-2.hari-1 respectivelly. The titanate synroc matrix materialscan succeed for immobilization of liquid radioactive waste containing of U, Cs and Sr elements, so that it is very good for immobilization for the radioactive waste generated from 99Mo production.